Organisational, Methodological and Economic Foundations for Creating Rural Resorts in the Hinterland of Sochi - Ryndin , Alexey V.; Platonov , Andrey. P.; Saryan , Akop A.; Kocharsky , Lev S. (Economy of Regions, 2022)
The resort city of Sochi includes both coastal and mountain tourist and recreational clusters. Nowadays, the city needs to involve natural and recreational resources and historical and cultural heritage assets of underdeveloped low-mountain areas and subtropical agricultural lands in the tourism industry. The present research aims to determine scientific, methodological and organisational foundations for sustainable development of the aforementioned areas. The study reveals the organisational, managerial and legislative aspects of the contradiction between the legal status of rural areas and recreational objectives of the Sochi resort. Co-development of both agricultural activities and most promising types of tourism in hinterland (namely, medical, agrarian, ethnic and cognitive tourism) will help overcome this contradiction. The socio-economic impact of tourism and infrastructure development in rural districts of Sochi will contribute to the increase in employment and entrepreneurship, as well as improve the welfare of indigenous people. Subsequently, due to the creation of rural resorts, the potential of balneological and natural curative resources, unique historical and cultural heritage, natural landscapes and subtropical agricultural lands can be fully realised. The research findings can be used to elaborate and implement sound programmes for the spatial development of rural resorts and agro-tourism destinations in Sochi. Further research will focus on possible ways to transform rural resources into factors for the production of an integrated tourist product with unique valuable properties.